''Amnarjaʿ la wara (We are going backwards)': Economic Reform and the politics of labour in agrarian Syria. Issue 2 (23rd February 2022) - Fernández, Sarkis
ABSTRACT: Drawing upon ethnographic research conducted in Syria between 2008 and 2011, this article explores the consequences of policies of economic reform and market liberalisation for agrarian relations of production in two different but interlinked agrarian contexts. The theoretical discussion of Marx's concept of subsumption is used as both a point of departure and arrival in the analysis. From this perspective, the Economic Reform emerges as a hegemonic project of rescaling and of reconstituting the subsumption of labour. This involved both a process of devaluation of agrarian work and workers' livelihoods, and of their disempowerment through the reorganisation of the state.